PENGARUH PENAMBAHAN LIMBAH NILON TERHADAP KUAT TEKAN DAN TARIK BELAH BETON UNTUK PEMBUATAN FIBER BETON - Tarsisius Sarman; Safrin Zuraidah; Budi Hastono (Fakultas Teknik, Universitas Wiraraja, 2026)
Concrete excels due to its high compressive strength, durability, and resistance to fire, water, and environmental factors. However, concrete has weaknesses in terms of low tensile strength and brittleness. The addition of fibers, such as nylon fibers, to the concrete mixture aims to overcome these weaknesses by providing randomly distributed reinforcement. This study examined the effect of adding nylon fibers at varying concentrations of 0% (normal), 2%, 4%, and 6% on the mechanical properties of concrete. The tests conducted included compressive strength (at 7, 14, and 28 days), as well as splitting tensile strength and porosity (at 28 days). The results of the 28-day testing showed that: Compressive Strength: The addition of nylon fibers effectively increased the compressive strength. The maximum value was obtained at a variation of 6% at 21.51 MPa, an increase of 11.8% compared to normal concrete (19.24 MPa). Split Tensile Strength: The addition of nylon fibers generally resulted in slightly lower values. The highest value for nylon variation was obtained at 6% at 2.55 MPa (a decrease of 1.9% from the normal 2.59 MPa). The 2% variation experienced the largest decrease, namely 2.22 MPa (a decrease of 15.1%)